Evaluasi Unjuk Kerja Alat Gali-Muat pada Kegiatan Penambangan Batubara di PT. Insani Bara Perkasa Site Kam 11 Loajanan Kalimantan Timur - Ruslan Patur; Harjuni Hasan; Henny Magdalena; Shalaho Dina Devi; Ardhan Ismail; Tommy Trides (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to evaluate the performance of the loading and unloading equipment in coal mining activities at the Mahakam Pit, PT Insani Bara Perkasa Site Km 11, East Kalimantan. The research was motivated by the importance of achieving mechanical equipment performance standards according to the Decree of the Minister of Energy and Mineral Resources No. 1827 of 2018. Data were obtained through direct observation and analysis of actual working time and evaluation of operational constraint factors. The results of the analysis showed that before the evaluation, the mechanical availability (MA) value was 87.24%, physical availability (PA) 88.51%, availability utilization (UA) 88.73%, and effective utilization (EU) 78.54%. After evaluating the constraint time, there was an increase in all parameters: MA to 88.71%, PA to 89%, UA increased to 90%, and EU reached 80%. This evaluation also had an impact on increasing the productivity of the loading and unloading equipment from 268.41 bcm/hour to 284.43 bcm/hour. Thus, the evaluation of work obstacles is proven to be effective in increasing the efficiency and productivity of the digging-loading equipment at the research location.